2020
DOI: 10.1016/j.jsxm.2020.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Kidney Transplantation on Male Sexual Function: Results from a Ten-Year Retrospective Study

Abstract: Background The effects of kidney transplantation on male sexual function are controversial. Aim To evaluate the impact of kidney transplantation on erectile and ejaculatory function and to assess a possible correlation between some selected characteristics of patients and their erectile and ejaculatory function after renal transplantation. Methods An observat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
0
9
0
1
Order By: Relevance
“…Many studies on sexual dysfunction in kidney transplant patients have focused on males. [25][26][27] Our study, to the best of our knowledge, is the first to show that post-transplant time and activity avoidance are associated with sexual dysfunction in female kidney transplant patients, which provides a theoretical basis for improving the sexual quality of life of those populations.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Many studies on sexual dysfunction in kidney transplant patients have focused on males. [25][26][27] Our study, to the best of our knowledge, is the first to show that post-transplant time and activity avoidance are associated with sexual dysfunction in female kidney transplant patients, which provides a theoretical basis for improving the sexual quality of life of those populations.…”
Section: Discussionmentioning
confidence: 70%
“…This association was observed in Spirito's study for male kidney transplant patients, 27 indicating that healthcare workers should also provide sex-related guidance in the early period of transplantation, in addition to focusing on allograft kidney function. Our study also showed that smoking (active and passive) was strongly associated with FSD in kidney transplant patients.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Previous studies have shown improvement in erectile dysfunction after kidney transplantation 14 , 15 but a recent study looked at both erectile and ejaculatory function prospectively in kidney transplant recipients. 16 The mean IIEF score significantly decreased at 6 months and was unchanged at 12 months after transplantation. Ejaculatory function, as assessed by the Male Sexual Health Quality-Ejaculation Disorders (MSHQ-EjD) short form, also decreased significantly at the 6- and 12-month follow-up.…”
Section: Sexual Function Post–kidney Transplantationmentioning
confidence: 89%
“…9 Epidemiological data and relevant nonsystematic, qualitative reviews do not comprehensively address this matter and render the effect of RT on EF controversial. 10,11 Within this framework, we systematically synthesized the available evidence and generated a meta-analysis, aiming to assess the effect of renal transplantation on erectile function and to determine potential factors improving or deteriorating erectile dysfunction.…”
mentioning
confidence: 99%